Insidensi dan Mortalitas Cedera Otak Traumatik di Rsud Prof. Dr. Margono Soekarjo Purwokerto Tahun 2021-2022 - Nabila, Fatya; Setiawan, Agus Budi; Nafiisah (State Islamic University of Sunan Ampel, 2024)
Traumatic brain injury is a serious health and socioeconomic problem worldwide, including Indonesia. The percentage of traumatic brain injury cases in Indonesia reached 11.9%. The severity of traumatic brain injury is assessed based on the Glassgow Coma Scale (GCS) and classified into mild, moderate and severe degrees. This study aims to determine the incidence and mortality of traumatic brain injury at Prof. Dr. Margono Soekarjo Hospital in 2021-2022. This research method is descriptive observational research uses secondary data with total sampling techniques and is presented in the form of percentage and frequency distribution tables. The number of samples obtained was 624 patients. The majority of cases were male patients (70.35%), age range 18-35 years (32.53%), elementary school education level (41.83%), with mild severity (63.94%), diagnosed with cerebral contusion (40.87%), no surgery (70.19%), and patient outcome did not die or improved (92.31%). The percentage of mortality or patients who died was 7.69%.